PENERAPAN PERLINDUNGAN HUKUM PEMEGANG HAK MEREK TERKENAL DI INDONESIA BERDASARKAN PROTOKOL MADRID - Mustika Sari; Elfrida Ratnawati (Ensiklopedia of Journal, 2023)
In the era of globalization, the economy is moving at a rapid pace, agreements made by ASEAN leaders resulted in the emergence of the single market or MEA (Asean Economic Community). This has led to market competition between countries in this region. Brand as a very important identity in the free market of a product, a brand can be a differentiator from one manufacturer to its competitors. With a brand that already has a good reputation in the community, it will increase the economic value of the brand and the brand will be easily recognized. Well-known brands generally have loyal consumers, manufacturers of these brands will find it easy to market their products, but this will be a trigger for unsavory individuals who want to make profits quickly without incurring large costs by counterfeiting well-known brands. So in the face of MEA (Asean Economic Community) it is necessary to have legal protection for well-known brands. In the midst of this unhealthy competition, the Madrid Protocol emerged as an easier and more efficient alternative to international registration of brands. In line with the essence of legal theory, legal development is a means of community development, meaning that all legal changes and reforms aim to create community welfare. There is also a need for outreach to prevent trademark infringement for both local brands wishing to register their brands abroad and consumers to clearly know the characteristics of counterfeit brands. The research method in this research is normative research using a conceptual approach and a statutory approach.Keywords: Well Known Mark, Madrid Protocol, Development Legal Theory